Study on Architectural Characteristic and Natural Environment Control System of Japanese Traditional House: Case Study Traditional Houses in Kitakyushu City, Japan - Dian Sekartaji; Bart Dewancker (Universitas Bandar Lampung (UBL), 2013)
Abstract — Japanese traditional housing, in its approach to harmony with natural surroundings and environment has formed as unique shape and philosophy which become Japan National property. In the other hand Japan traditional house recently becomes not popular in Japan while Japanese contemporary house has technology method for controlling its environment. However high technology needs more energy to consume and this causes the other problem of environment. This study of traditional houses, located in Kitakyushu City, aims to investigate the architectural characteristic of Japanese traditional house such as structure, plan, material, and natural environment control system. In the beginning, two traditional houses have been selected as target of study; those are Takasaki Old Residence and Shimizu Old Residence in Yahata Nishi Ward. The first section is devoted to the analysis of basic form and structure in three traditional houses. In the following section, the study examines methods used to control the architectural environment in Japanese traditional house which we can call natural environment control system. In conclusion, a preliminary outline of the architectural characteristic and natural environment control system analysis are given. Moreover, the result of this study can be expected become inspiration for recent house construction.